NLRP3 Inflammasome: Checkpoint Connecting Innate and Adaptive Immunity in Autoimmune Diseases - Zhang, Yiwen; Yang, Wenlin; Li, Wangen; Zhao, Yunjuan (Frontiers in Immunology, 2021)
Autoimmune diseases are common immune system diseases which are characterized by the breakdown of immune tolerance and the production of autoantibodies. In recent studies, the dysfunction in innate and adaptive immune system is considered to be key step in the initiation and maintenance of autoimmune diseases. NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a multimeric protein complex, which can detect exogenous pathogen irritants and endogenous danger signals. The main function of NLRP3 inflammasome is to promote secretion of proinflammatory cytokines interleukin (IL)-1β and IL-18, and pyroptosis mediated by caspase-1. Served as a checkpoint in innate immunity and a switch to trigger adaptive immune dysfunction, aberrant activation and regulation of NLRP3 inflammasome plays an important role in the pathogenesis of autoimmune diseases. This paper reviewed potential effect of NLRP3 inflammasome in autoimmune diseases, which shows NLRP3 inflammasome may be a potential target for autoimmune diseases deserved further study.